Ocean waves and oscillating systems : linear interactions including wave-energy extraction - Falnes, Johannes, 1931- (Cambridge University Press, 2002)
This book examines the interaction between ocean waves and oscillating systems. With a focus on linear analysis of low-amplitude waves, the text is designed to convey a thorough understanding of wave interactions. Graduate students and researchers will find it an excellent source of wave energy theory and application.